Density and diversity of breeding birds in forests in the province of Ångermanland - Risberg, Birger (Ornis Svecica, 1997)
The aim of this study was to estimate density and diversity of breeding birds in ordinary managed forests in the northern Swedish province of Ångermanland. The field work was performed during four breeding seasons within the period of 1989 to 1994. A territorial survey method, with fixed study areas, was used. 41 survey areas with a total area of 623.8 ha were censused representing 0.4 per mile of the woodland in Ångermanland. The mean density was 139 breeding pairs/km2 (median 124 pairs/km2). 53 different bird species were considered breeding in the 41 survey areas. Chaffinch, Willow Warbler and Robin were the most abundant species. These three species accounted for 36% of the total amount of territories. The lowest density and diversity was found in clear cuts and plant stands (90 pairs/km2; 21 different species) while the highest was recorded in middle aged stands (165 pairs/km2; 34 species). Game birds and birds of prey were found breeding only in mature and middle aged stands. The abundance of most tits and woodpeckers were highest in mature stands.